Nursing process in the everyday life of nurses in Psycho-Social Attention Centers - Paula Fernanda Lopes; Ana Paula Rigon Francischetti Garcia; Vanessa Pellegrino Toledo (Universidade Federal do Ceará, 2014)
This study aimed at understanding the achievement of Nursing process in the everyday life of the nurse in Psychosocial Attention Centers. This was a qualitative study, including data collected by means of semi-structured interviews, from April to May 2012, in Campinas, São Paulo, Brazil, with nine nurses. From the data analysis, three thematic categories arouse: the Nursing process understood as assistance systematization; the difference in the nursing work process in the different mental health equipment; and the dichotomy between body and mind. The Nursing process is carried out as performance of the data collection instrument. The lack of clarity of the nursing role in the multi-professional team is an obstacle to the elaboration of an individual therapeutic project, resulting in difficulties to incorporate the concept of integrality and therapeutic interpersonal relationship for the preparation of the Nursing process.